1987
DOI: 10.1099/0022-1317-68-10-2615
|View full text |Cite
|
Sign up to set email alerts
|

Immunogold Detection of Polyhedrin, p10 and Virion Antigens in Autographa californica Nuclear Polyhedrosis Virus-infected Spodoptera frugiperda Cells

Abstract: SUMMARYProtein A-gold labelling was used to detect and locate particles and two major late antigens, polyhedrin and pl0, of Autographa californica multiply-enveloped nuclear polyhedrosis virus in thin sections of Spodoptera frugiperda cells. With polyhedrin antiserum, gold label was found over viral occlusion bodies (polyhedra), but not over the fibrous structures associated with polyhedron morphogenesis and previously thought to consist of precondensed polyhedrin. In contrast, with pl0 antiserum, gold label w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

1989
1989
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 18 publications
1
41
0
4
Order By: Relevance
“…5b) have been seen to accumulate in the cytoplasm and nucleus of cells infected with nuclear polyhedrosis viruses (Harrap, 1970;MacKinnon et al, 1974;Chung et al, 1980). The speculation that p 10 is a major component of these structures is supported by recent immunocytochemicat observations (van der Wilk et al, 1987) and the finding that the structures are absent in cells infected with the pl0 deletion mutants (Fig. 6, 7).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…5b) have been seen to accumulate in the cytoplasm and nucleus of cells infected with nuclear polyhedrosis viruses (Harrap, 1970;MacKinnon et al, 1974;Chung et al, 1980). The speculation that p 10 is a major component of these structures is supported by recent immunocytochemicat observations (van der Wilk et al, 1987) and the finding that the structures are absent in cells infected with the pl0 deletion mutants (Fig. 6, 7).…”
Section: Discussionsupporting
confidence: 63%
“…as a discrete structure. Van der Wilk et al (1987) speculated that the cytoplasmic accumulations may act as reservoirs of pl0. However, Quant-Russell et al (1987) demonstrated a crossreactivity of some pl0 monoclonal antibodies to the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4c). The association of pl0 with fibrillar structures has also been reported for the AcMNPV by van der Wilk et al (1987). The pl0 MAb also was associated with virions and polyhedra (Fig.…”
Section: Pio : Cross-reaction Of the Plo Mab With A Cellular Proteinmentioning
confidence: 49%
“…Similar structures were observed within the cell bodies of all control cells infected either with wild type virus or beta-galactosidase inserts . It looked very similar to the fibrous virally encoded p10 protein present in the cell bodies of the infected cells (Van Der Wilk et al ., 1987), with the exception that the material in the processes was kept within straight boundaries. It is therefore possible that the electrondense structure represents the p10 viral gene product .…”
Section: Ultrastructure Of Tau-induced Processesmentioning
confidence: 83%